2013
DOI: 10.1007/s10961-013-9322-y
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of national patent ownership by public research organisations and universities

Abstract: This paper focuses on the question of whether the national production functions of patents owned by universities and public research organisations (PROs) differ. We use Eurostat patent and R&D data broken down by institutional sector for the European Union 27 and other countries in years 1982-2007, and we estimate dynamic panel models. The impact of R&D expenditure on patent ownership is higher for PROs than for universities. University patent ownership activity is dependent on business funding, while PRO pate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Funding is a significant element that defines patent ownership in partnerships. In fact, Azagra-Caro (2014), using Eurostat patent data for the 27 European Union countries, demonstrates that, in general, dependence on public or private funding defines how STIs or companies create technology.…”
Section: Discussionmentioning
confidence: 99%
“…Funding is a significant element that defines patent ownership in partnerships. In fact, Azagra-Caro (2014), using Eurostat patent data for the 27 European Union countries, demonstrates that, in general, dependence on public or private funding defines how STIs or companies create technology.…”
Section: Discussionmentioning
confidence: 99%
“…This control competence over technological research is easier for university-owned patents than for university-invented patents because the former relies on university's resources while the latter are totally or partially funded by the firms that end up owning the intellectual property. Some empirical research supports this idea; for example, university-owned patents have been found to be more responsive to public funding and university-invented patents more responsive to private funding (Azagra-Caro et al 2006a;Azagra-Caro 2014).…”
Section: University-owned Patents Across European Universitiesmentioning
confidence: 99%
“…Research suggests that PROs commercialise their research outcomes through a variety of KT channels, among others, research contracts, consultancy services, prototyping, testing, personnel secondment, sharing of physical facilities, public engagement, outreach activities, spinning off companies (Neresini and Bucchi 2011;Smith 2015;Hughes et al 2016a;Hallonsten et al 2020), and patent filing and licensing-the latter being the most extensively investigated KT channel in the case of PROs (Azagra-Caro 2011Rossi and Athreye 2021).…”
Section: Antecedents To Pros' Kt Engagement and The Role Of Field Of ...mentioning
confidence: 99%
“…They also face growing pressures to diversify their income streams in the context of shrinking public funding (Maxwell-Jackson 2011;Archibugi and Filippetti 2018). Consequently, PROs increasingly strive to transfer knowledge to external stakeholders, both to derive additional income and to demonstrate their economic and societal relevance (Lyall et al 2004;Dutrénit and Arza 2010;Rossi and Athreye 2021).Research suggests that PROs commercialise their research outcomes through a variety of KT channels, among others, research contracts, consultancy services, prototyping, testing, personnel secondment, sharing of physical facilities, public engagement, outreach activities, spinning off companies (Neresini and Bucchi 2011;Smith 2015;Hughes et al 2016a;Hallonsten et al 2020), and patent filing and licensing-the latter being the most extensively investigated KT channel in the case of PROs (Azagra-Caro 2011Rossi and Athreye 2021).Nonetheless, the combinations of KT resources and channels that PROs deploy, and how these relate to the PROs' organisational characteristics, have not yet been investigated. Studies of universities have shown that different types of universities develop different profiles of KT engagement, which correlate with their research and teaching intensity (e.g.…”
mentioning
confidence: 99%